Blunt cardiac injury without external evidence of thoracic trauma: A report of two pediatric cases. (16th February 2016) - Monroe, Dustin E; Willert, Jennifer; Saba, Ziad; Rosenfeld, Howard; Willis, Brigham C
Objective: To report two cases of cardiac injury following blunt thoracic trauma without external evidence of injury. Design: Case report and review of the literature. Setting: A 23-bed pediatric intensive care unit in an academic children's hospital. Interventions: Two children presented following significant thoracic trauma without external evidence of injury. Cardiac injury was not initially suspected, and lack of definitive diagnostic evaluation led to a delay in diagnosis and definitive treatment. Results: A 4-year-old girl presented 6 months after initial injury and evaluation with massive right ventricular dilatation secondary to traumatic tricuspid regurgitation. The second patient, an 11-year-old boy, underwent a laparotomy for suspected abdominal pathology delaying diagnosis of his traumatic ventricular septal defect and definitive repair until clinical hemodynamic deterioration occurred. Conclusion: Clinicians should maintain a high index of suspicion for cardiac injury in patients with a significant mechanism of thoracic trauma despite external evidence. Standard screening tests are often inadequate and echocardiography should be performed for any suspected cardiac trauma.